The Level of Public Purchasing Power on the Decision to Purchase Halal Products in North Sumatra - Harahap, Faisal Hamdani; Nasution, Muhammad Syukri Albani; Nurbaiti, Nurbaiti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Indonesia is a country with a very large market share for sharia economy-based products and services. The development of the halal product industry in Indonesia from year to year is increasingly significant. It cannot be denied that research related to halal products is always interesting to study and analyze more deeply, especially from the consumer's perspective. Therefore, this research aims to analyze how Income, Taste, and Price influence the Decision to Purchase Halal Products in North Sumatra Province with Interest as an Intervening Variable. This research is quantitative research with verification research methods. The sample taken was 100 Muslim participants who live in North Sumatra. provided that participants have purchased or are currently using halal products. This research has the results that Income, Taste, and Price partially influence interest in halal products in North Sumatra Province. Interest influences the decision to purchase halal products in North Sumatra Province. Income, tastes and prices both partially and simultaneously influence Halal Product Purchasing Decisions in North Sumatra Province with Interest as an Intervening Variable. Based on the analysis, it appears that the three factors, namely income, price, and people's tastes, have a significant impact on shaping consumer preferences. The relationship between income, product prices, and tastes creates complex dynamics that influence people's purchasing decisions for halal products.